(untitled) (Heritage, 2023)
Artificial intelligence has largely become an integral part of our lives. It has found its application in all spheres of modern life, from the virtual personal assistant that helps us organize our working day, through traffic control, the use of autonomous vehicles, through the inevitable use in medicine, education, agriculture, but also in restoration, preservation and promotion. cultural heritage. Artificial intelligence and machine learning have enormous potential in the (semi)automatic selection, organization and preservation of cultural heritage in libraries, archives and museums, as well as in the computer analysis of cultural heritage data.